2017
DOI: 10.1192/bjp.bp.117.208397
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive periods for the effect of childhood interpersonal violence on psychiatric disorder onset among adolescents

Abstract: Background Although childhood adversity is a strong determinant of psychopathology, it remains unclear whether there are ‘sensitive periods’ when a first episode of adversity is most harmful. Aims To examine whether variation in the developmental timing of a first episode of interpersonal violence (up to age 18) associates with risk for psychopathology. Method Using cross-sectional data, we examined the association between age at first exposure to four types of interpersonal violence (physical abuse by par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…There is mounting evidence showing that childhood adversity is associated with high levels of general psychopathology, both cross-sectionally and prospectively (Green et al, 2010;Dunn et al, 2017;McLaughlin et al, 2012). This link tends to span all forms of psychopathology, including both internalizing and externalizing domains (Salum et al, 2016) -and therefore associations with general expressive indexes of psychopathology (such as the "p" factor) are expected (Miller et al, 2016), as we confirmed here.…”
Section: Discussionsupporting
confidence: 81%
“…There is mounting evidence showing that childhood adversity is associated with high levels of general psychopathology, both cross-sectionally and prospectively (Green et al, 2010;Dunn et al, 2017;McLaughlin et al, 2012). This link tends to span all forms of psychopathology, including both internalizing and externalizing domains (Salum et al, 2016) -and therefore associations with general expressive indexes of psychopathology (such as the "p" factor) are expected (Miller et al, 2016), as we confirmed here.…”
Section: Discussionsupporting
confidence: 81%
“…As a result of ACEs, lower rates of engagement at school are also more likely [ 45 , 101 ] and there is an increased risk for learning- and behavioral issues and suicidal ideation [ 55 ]. Adolescence is a unique developmental stage, characterized by rapid growth in which physiologic, cognitive, social and emotional changes occur simultaneously, and ACEs may impede this development [ 55 , 102 ]. Finally, accumulation of ACEs can increase the risk of psychotropic medication in adolescents [ 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early adversity and trauma such as interpersonal violence and beating are now established as a cause of later mental illnesses and behavioural disorders; there is also an elevated risk of substance use among adolescents who were beaten by someone. 2 Childhood trauma is associated with gender-based violence and childhood maltreatment. 3 Some reports suggest child abuse may affect women's risk of developing psychosis more than that of men, although young boys and men can also be susceptible to the lifetime consequences of violence and abuse.…”
Section: Early Prevention and Treatmentmentioning
confidence: 99%
“…In this context, and awareness of the growing global burden of neuropsychiatric disorders, prevention and treatment responses should be aligned in promoting safer and more protective early-life environments for children and women. Early adversity and trauma such as interpersonal violence and beating are now established as a cause of later mental illnesses and behavioural disorders; there is also an elevated risk of substance use among adolescents who were beaten by someone 2 . Childhood trauma is associated with gender-based violence and childhood maltreatment 3 .…”
Section: Early Prevention and Treatmentmentioning
confidence: 99%